PEMANFAATAN KAIN PERCA UNTUK PEMBUATAN MASKER KAIN (MAIN) ANTI VIRUS DALAM RANGKA PENCEGAHAN VIRUS COVID 19 PADA RUMAH JAHIT SEKITARAN MEDAN JOHOR - Wardiyah Daulay; Mahnum Lailan Nasution; Sri Eka Wahyuni (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
The number of cases of the Covid-19 virus in Indonesia, especially Medan, has increased. Almost every day the number of PDP (Patients Under Supervision) or positive patients continues to increase. Medan city has set an emergency status for the corona Covid-19 virus since Mid-March and Medan Johor district sice early April has been designated as one of the sub-districts with the status of the Red Zone. To minimize its spread, the government is promoting a “Mask For ALL” program. The program is in line with the appeal of the centers for disease control and prevention, which recommends wearing masks for everyone who want to leave the house. Due to limited number of masks that are ideal for preventing the corona virus, cloth masks can also used as an option to protect against exposure to the corona virus. This is considered better than not wearing a mask at all when coughing and sneezing or when near other people who may have been infected with the corona virus. Fabric masks can be produced by sewing houses by using the patchwork they have. Becauses the materials in making masks do not require a lot of material, patchwork can be used and people who have sewing houses are also helped in the corona pandemic.